Unified Power Quality Conditioner Using Injection Capacitors for Voltage Sag Compensation - Madhusmita Patro; Kanhu Charan Bhuyan (International Journal of Applied Power Engineering (IJAPE), 2017)
Power quality has become an important factor in power systems, for consumer and household appliances. The main causes of poor power quality are har ue of achieving active current distortion compensation, power factor monic currents, poor power factor, supply voltage variations etc. A techniq correction and also mitigating the supply voltage variations at load side is compensated by unique device UPQC presented in this thesis. This concept presents a multi loop based controller to compensate power quality problems through a three phase four wire Unified Power Quality Conditioner (UPQC) under unbalanced and distorted load conditions. Here the UPQC is constituted of two Voltage Source Converters (VSC) connected via power link. The series compensator is connected to the line in series and injects the voltage and thus compensates for voltage issues; whereas the shunt compensator injects current thus compensating for current issues, and is connected in shunt to the line. The voltage injection to the line uses an ijecting transformer. The injection transformer is later replaced with injection capacitors, thus eliminating the drawback of conventional UPQC. In this way a good power quality is maintained